Hint of Lyme, an uncommon cause of syncope. (6th March 2014) - Manek, Megha; Kulkarni, Abhishek; Viera, Anthony
Abstract : A 20-year-old Caucasian male patient presented after a single episode of syncope. His heart rate was 40 beats per minute. ECG showed new onset complete heart block. A temporary pacer was placed. He had a macular rash on the body from past 2 weeks and was diagnosed with contact dermatitis. Erythema migrans was considered as differential for rash. Lyme titre was ordered and found to be positive. After antibiotic therapy and observation on telemetry, his heart block resolved. He was subsequently discharged and a follow-up ECG revealed persistent normal sinus rhythm.